2018
DOI: 10.1089/tmj.2017.0211
|View full text |Cite
|
Sign up to set email alerts
|

Remote Presence Robotic Technology Reduces Need for Pediatric Interfacility Transportation from an Isolated Northern Community

Abstract: RPRT reduced the need for specialized pediatric IFT, while enabling regionalization when appropriate. This study may have implications for the broader implementation of RPRT, while reducing costs to the healthcare system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 31 publications
1
26
0
1
Order By: Relevance
“…In an additional study within a remote First Nations community in northern Saskatchewan, 63% of acutely ill children assessed by RPT were safely treated within their home community and did not need to be transported to tertiary level hospitals to receive care. The use of RPT in this study also demonstrated considerable savings in the care of these children by reducing transport and hospital admission costs [17]. Because the RPT creates a sense that the remote physician is present at the patient's bedside, can facilitate collaborative treatment plans and can be used to promote self-determined approaches to healthcare priorities, this technology offers the potential to deliver culturally safe specialised emergency and paediatric care to communities throughout Canada's North [34].…”
Section: Future Directionsmentioning
confidence: 80%
See 1 more Smart Citation
“…In an additional study within a remote First Nations community in northern Saskatchewan, 63% of acutely ill children assessed by RPT were safely treated within their home community and did not need to be transported to tertiary level hospitals to receive care. The use of RPT in this study also demonstrated considerable savings in the care of these children by reducing transport and hospital admission costs [17]. Because the RPT creates a sense that the remote physician is present at the patient's bedside, can facilitate collaborative treatment plans and can be used to promote self-determined approaches to healthcare priorities, this technology offers the potential to deliver culturally safe specialised emergency and paediatric care to communities throughout Canada's North [34].…”
Section: Future Directionsmentioning
confidence: 80%
“…Primary healthcare within many remote and isolated communities in northern Canada is provided by community healthcare centres that are primarily staffed by nurses and supported by periodically visiting physicians. These healthcare centres can experience high staff turnover and inconsistent access to physicians and lack of access to healthcare providers with specialised expertise in fields such as emergency medicine and paediatrics [5,8,17]. Patients who require specialised medical care are routinely required to travel to regional hospitals or tertiary centres hundreds or thousands of kilometres away.…”
Section: Challenges Of Accessing Healthcare In Canada's Northmentioning
confidence: 99%
“…A recent pilot study looking at triaging paediatric acute care transports in the province of Saskatchewan revealed that direct assessment and triaging with remote presence robotic technology significantly decreased the number of respiratory patients requiring transport out of their home communities [6]. Remote presence robotic technology has the potential for significant cost-benefit from a reduction in medical transport expenses.…”
Section: Current Uses In Northern Rural and Remote Communitiesmentioning
confidence: 99%
“…Telemedicine reduces the need for interfacility transfer from both rural communities as well as community hospitals with hospitalist programs . 47,48,[51][52][53] This positive affect has significant influence on the feasibility of systemization of care for pediatric patients as well as stress of the limited subspecialty pediatric workforce.…”
Section: Accepted Manuscriptmentioning
confidence: 99%